Determination of Level of Termination of Spinal cord (conus medullaris) in MRI - Paudel, Sharma; Kayastha, Prakash; Joshi, Gobind Prasad; Joshi, Sweta; Regmi, Pradeep Raj; Paudyal, Sudil (Nepal Journal of Medical Sciences, 2024)
Introduction: The termination of the conus medullaris is a crucial anatomical landmark in anatomy, and its exact location and variability are of great clinical significance. By knowing the exact location of the conus medullaris, we can avoid injury to the spinal cord during spinal procedures like spinal anesthesia, lumbar puncture, lumbar myelography, CSF sample collection, and others. Methodology: The level of spinal cord termination was assessed from the mid-sagittal section of the T2 weighted MRI images. A total of 270 patients referred for MRI examinations of the lumbar spine for various clinical indications to the Radiology Department of Tribhuvan University Teaching Hospital (TUTH) were selected for the study. Result: The most common level of termination of the spinal cord was found to be the L1/L2 intervertebral disc (77 patients). The level of termination of the spinal cord ranged from the lower 1/3rd of T12 vertebrae to the L2/L3 intervertebral disc. There was no statistically significant difference in the level of termination of the spinal cord with gender (p>0.05). There was a mild positive correlation between the level of termination of the spinal cord and age, which was statistically significant (r=0.22, p=0.001). Conclusions: In this study, we studied the level of spinal cord termination in MRI and the most common level was found at the L1/L2 intervertebral disc.